Food preparation methods, drinking water source, and esophageal squamous cell carcinoma in the high-risk area of Golestan, Northeast Iran. Issue 2 (March 2016) - Golozar, Asieh; Etemadi, Arash; Kamangar, Farin; Fazeltabar Malekshah, Akbar; Islami, Farhad; Nasrollahzadeh, Dariush; Abedi-Ardekani, Behnoosh; Khoshnia, Masoud; Pourshams, Akram; Semnani, Shahriar; Marjani, Haji Amin; Shakeri, Ramin; et al.
Abstract : Cooking practices and water sources have been associated with an increased risk of cancer, mainly through exposure to carcinogens such as heterocyclic amines, polycyclic aromatic hydrocarbons, and nitrates. Using data from the Golestan case–control study, carried out between 2003 and 2007 in a high-risk region for esophageal squamous cell carcinoma (ESCC), we sought to investigate the association between food preparation and drinking water sources and ESCC. Information on food preparation methods, sources of drinking water, and dietary habits was gathered from 300 cases and 571 controls matched individually for age, sex, and neighborhood using a structured questionnaire and a semiquantitative food frequency questionnaire. Multivariate conditional logistic regression was used to estimate odds ratios (OR) and 95% confidence intervals (CI) adjusted for potential confounders and other known risk factors including socioeconomic status and smoking. More than 95% of the participants reported eating meat, mostly red meat. Red meat consumption above the 75th percentile increased the odds of ESCC by 2.82-fold (95% CI: 1.21–6.57). Fish intake was associated with a significant 68% decrease in ESCC odds (26%, 86%). Among meat eaters, ORs (95% CI) for frying meat (red or white) and fish were 3.34 (1.32–8.45) and 2.62 (1.24–5.5). Drinking unpiped water increased ESCC odds by 4.25 times (2.23–8.11). The OR for each 10-year increase in the duration of drinking unpiped water was 1.47 (1.22–1.78). Our results suggest roles for red meat intake, drinking water source, and food preparation methods in ESCC, even after adjusting for a large number of potential confounders.